Physico-chemical and Textural Properties of Gelatins and Water Gel Desserts Prepared from the Skin of Freshwater Carps - Ninan, George; Zynudheen, A A; Joseph, Jose (Fishery Technology, 2025)
The physico-chemical properties of fish skin gelatins extracted from cultured freshwater carps viz., rohu, common carp and grass carp, were investigated and compared with commercial food grade mammalian skin gelatins. Water gel desserts prepared from these gelatins were analysed for physical properties and texture profile. Among the fish skin gelatins, grass carp skin gelatin had the highest gel strength of 230 Bloom followed by rohu skin gelatin (188 Bloom) and common carp skin gelatin (181 Bloom). The melting point of fish skin gelatins was in the range of 28.13 – 29.10OC which was found to be higher than that reported for gelatin from many other species of fish. Carp skin gelatin desserts had significantly lower melting point than the mammalian skin gelatin desserts which can help in better flavour release in dessert preparations. Grass carp skin and bovine skin gelatin desserts had similar gel strength, cohesiveness and springiness. Carp skin gelatin desserts had less off odour compared to mammalian skin gelatin desserts.